Numerical investigation on the supersonic flow around a saboted bullet - Nguyen, Quang Tuan; Nguyen, Hai Minh; Bui, Xuan Son (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: In this paper, the aerodynamic characteristics of a special bullet were investigated at supersonic conditions. A model of a handgun saboted bullet was selected for the study. Methods: The method used in the research was computational fluid dynamic (CFD) simulation. The turbulence model k-ε was used for numerical calculation. The air model was selected as an ideal gas. For air viscosity, the Sutherland model was applied. Results: The numerical simulation results show the behavior of the supersonic flow over the saboted bullet. By varying the petals opening angle and bullet velocity, their influences on the drags of the sabot and the penetrator were obtained to be used for later sabot separation study. Conclusion: The study shows that the CFD simulation approach can be implemented to analyze the aerodynamic drags on the sabot and the penetrator after the saboted bullet leaving the gun barrel. The simulation results obtained in this work are important in designing saboted light armor-piercing bullets fired from handguns.